Adjuvant radiotherapy for cervical cancer in South Korea: a radiation oncology survey of the Korean Radiation Oncology Group (KROG 20-06). (29th March 2021) - Kim, Nalee; Park, Won
Abstract: Objective: Radiation therapy plays an important role in adjuvant treatment for surgically treated cervical cancer with adverse pathological findings. This was the first study to evaluate current practices of adjuvant radiation therapy among centres affiliated with the Korean Radiation Oncology Group. Methods: A survey containing specific questions on the demographics in 2019, indications of adjuvant treatment, radiation therapy field, prescription radiation therapy dose, boost radiation therapy and chemotherapy was sent out by e-mail to 93 centres. Results: The overall response rate was 62.4%. Regarding radiation therapy techniques, intensity-modulated radiation therapy was adopted in most institutions (41/58, 70.7%). Various risk group criteria were selected for adjuvant radiation therapy and concurrent chemoradiation therapy. One or two risk factors among tumour size, depth of invasion and lymphovascular invasion were considered for adjuvant radiation therapy by 20.7 and 60.3% of the respondents, respectively. The following criteria for concurrent chemoradiation therapy were considered by 60.3% of the respondents: parametrial extension, positive resection margin or lymph node metastasis. Various upper borders were preferred for pelvic radiation therapy by the institutions, and a total dose of 50.4 Gy in 28 fractions was the most prescribed dose scheme (37/58, 63.8%). Lymph node bed boost radiation therapy and vaginal cuff brachytherapy were considered for selected patients by 22.4% (13/58) and 60.3% (35/58) of the institutions. Conclusion: This survey demonstrated the practice patterns of adjuvant treatment that are prevalent in the field of radiation oncology among members of the Korean Radiation Oncology Group. These findings warrant further consensus on radiation therapy guidelines in the context of adjuvant treatment for cervical cancer. Abstract : The current study evaluated the various patterns of adjuvant treatment in surgically resected cervical cancer in South Korea.